Is it necessary to centralize power in the CEO to ensure environmental innovation? - Beatriz Aibar-Guzmán; José-Valeriano Frías-Aceituno (Administrative Sciences, 2021)
Using data from a sample of 4863 international firms corresponding to the period 2002-2017, this paper examines the role that chief executive officer (CEO) power plays in environmental innovation and the impact that these strategies have on financial performance. Both issues have been the subject of considerable debate in the literature, with opposite views and contradictory findings. The results indicate that investing in environmental innovations related to the use of clean technologies, ecological production processes, and the design, manufacture and commercialization of environmentally sustainable products requires that CEOs have a greater degree of power in order to support projects that do not entail a higher return in the short and medium terms. Additionally, the results show that the negative economic effect of eco-innovation reverses in the fourth and fifth years after environmental innovations were implemented. Thus, this study supports the view regarding a "bright side" of CEO power with regard to corporate sustainability.
Keywords: 350; environmental innovation; CEO ability; CEO power; eco-innovation; financial performance; upper echelon theory